2020
DOI: 10.1002/mds.28219
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Blind, Randomized, Placebo‐Controlled Trial of DA‐9701 in Parkinson's Disease: PASSGI Study

Abstract: A BS TRACT: Objectives: This study aimed to assess the efficacy of DA-9701 on gastrointestinal symptomrelated quality of life in patients with Parkinson's disease on stable dopaminergic medications. Methods: This multicenter, double-blind, placebo-controlled, phase 4 trial included a total of 144 patients with Parkinson's disease with gastrointestinal dysfunctions based on predefined criteria. Participants were randomized to take either DA-9701 or placebo for 4 weeks, and then both groups were administered DA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Demographic factors, co-morbidity, and other lipid levels were previously described 24 and did not differ between patients with PD and controls. In contrast, the Wexner constipation score and Korean version of the Non-Motor Symptom Scale (K-NMSS) scores were significantly higher in patients with PD than in controls (Table 1 ).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Demographic factors, co-morbidity, and other lipid levels were previously described 24 and did not differ between patients with PD and controls. In contrast, the Wexner constipation score and Korean version of the Non-Motor Symptom Scale (K-NMSS) scores were significantly higher in patients with PD than in controls (Table 1 ).…”
Section: Resultsmentioning
confidence: 77%
“…Patients were diagnosed with PD according to the United Kingdom Parkinson’s Disease Society Brain Bank Clinical Diagnosis Criteria 45 . The inclusion criteria were as follows: patients not receiving antibiotics, immune-related drugs, and vaccines (for 3 months), lipid-lowering drugs (for 1 month), and vitamin supplements, n-3 fatty acids, prebiotics, and probiotics (for 2 weeks) 24 . The exclusion criteria were as follows: patients with secondary parkinsonism, other significant central nervous system diseases, malignancy within the last 3 years, and significant gastrointestinal disorders 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with the plant-based prokinetic DA-9701 for 12 weeks improved dyspepsia severity scores in a double-blind randomized placebo-controlled trial (DB-RPCT) (n = 144), and no serious adverse events were reported. 41 H. pylori infection, which has been causatively linked to dyspepsia, peptic ulcer disease, and gastric carcinoma, is a major public health issue worldwide, especially in Asia, Africa, and Latin America. 42 Guidelines recommend that patients with dyspepsia (with or without red flag symptoms) should undergo H. pylori testing, which is easily performed using a non-invasive 13 C urea breath test or a stool antigen test.…”
Section: Dyspepsia and Helicobacter Pylori Infectionmentioning
confidence: 99%
“…However, specific evidence in PD is relatively lacking (Table 1). 4,15,41,[61][62][63][64][65][66][67] Domperidone is a peripheral dopamine D2 receptor antagonist that is relatively impermeable to the bloodbrain barrier, and it is a commonly used prokinetic agent. Domperidone improved GE time, gastroparesis symptoms and levodopa bioavailability in two small studies in PD.…”
Section: Gastroparesismentioning
confidence: 99%